Sustainable Ways for Early-Stage Startups to Build Scalable Business Models Leveraging AI in the Post-Pandemic Era - Karur Gurudaas, Radhakrishnan (Digital Repository of Theses, 2025)
The disruption caused by the COVID-19 pandemic has made it increasingly difficult for early-stage startups to survive, let alone scale. Many of these new ventures have been forced to reevaluate their business models in the face of sudden shifts in the market and widespread uncertainty. In this study, the spotlight is on artificial intelligence (AI) as a potential enabler of sustainable growth. Drawing on primary data collected from 70 startup founders and senior leaders; the research explores both the practical uses and persistent obstacles tied to AI adoption in startup settings. The analysis suggests that the startups that have made the most meaningful progress are those that align their technical efforts with clear strategic objectives and invest in organizational readiness, rather than focusing solely on the technology itself. The study contributes new, actionable insights for entrepreneurs, investors, and policymakers seeking to drive startup growth responsibly and adaptively as the business environment continues to change. Keywords: artificial intelligence, business model innovation, startups, scalability, sustainability, post-pandemic, entrepreneurship.